Mini Basketball Game Model to Improve Social Skill, Motoric Skill, and Physical Fitness of Elementary School Students - Supriyadi Supriyadi (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The aim of the study was to obtain a valid, practical and effective basketball game model to improve social skills, motor skills and physical fitness of elementary school students. This study uses a research and development design. The results showed that the mini basketball game had a significant positive effect on social skills, motor skills and physical fitness. So it can be concluded that the Mini Basketball game is a valid, practical, and effective game to improve social skills, motor skills, and physical fitness of elementary school students.Abstrak: Penelitian ini bertujuan untuk memperoleh model permainan bolabasket yang valid, praktis, dan efektif untuk meningkatkan keterampilan sosial, keterampilan motorik, dan kebugaran jasmani siswa SD. Penelitian ini menggunakan rancangan penelitian dan pengembangan. Hasil penelitian menunjukkan bahwa pada uji coba permainan bolabasket mini memiliki pengaruh yang signifikan positif terhadap keterampilan sosial, keterampilan motorik dan kebugaran jasmani. Dengn demikian, dapat disimpulkan permainan Bolabasket Mini merupakan permainan yang valid, praktis, dan efektif untuk meningkatkan keterampilan sosial, keterampilan motorik, dan kebugaran jasmani siswa SD.